Political Configuration of Islamic Law in Legal Development in Indonesia - Sanusi, Nur Taufiq; Fauzan, Ahmad; Syatar, Abdul; Kurniati, Kurniati; Hasim, Hasanuddin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
Indonesia's multicultural society influences legal policy in the development of the country from philosophical, cultural, social, and religious aspects. The current development of customary law, commonly referred to as al-dah al-muhakkamah, strongly supports national law as a source of law and is used by the Indonesian Islamic community along with customary law as its legal basis. Both are designed to provide legal benefits for the Indonesian people. This study focuses on the synchronization of Islamic law and national law to create a national law that is in harmony with the existing law in society through normative legal investigation methods and comparative legal approaches. The method used is qualitative method. The procedural model is a research technique that gathers verbal or written descriptions from sources in order to apply normative comparison techniques. The research results show Islamic law in the development of national law is the answer to the democratization of various sources of law in Indonesia. That is, national sources of law need to pay attention to the basic philosophy of Islamic law, which can answer and solve substantive and formal legal problems as the basis for the development of national law. The formalization of Islamic law in the context of the policy development of law or the development of Islamic law (legal structure) in the development of national law is not sufficiently limited to mere formalization but to its nature and content. امللخص يؤثر المجتمع متعدد الثقافات في إندونيسيا على السياسة القانونية في تطور البلاد من الجوانب الفلسفية والثقافية والاجتماعية والدينية. إن تطوير القانون العرفي الذي يشار إليه عادة باسم